Lymphocyte count in peripheral blood is a sensitive tool in pretreatment assessment of patients with urological cancer - Yakovlev, P.; Klyushin, D. (Experimental Oncology, 2018)
Cancer, inflammation and immune surveillance recruit lymphocytes as common key cellular players. The aim of the study was to assess a utility of the absolute and relative lymphocyte counts (ALC and RLC) in peripheral blood of patients with urological cancer as sensitive tool in pretreatment assessment of patient, which correlates with postoperative outcome of the disease, and outlines the overall reactivity of the patient. Materials and Methods: We retrospectively studied correlation between lymphocyte count in peripheral blood of the patients with urological cancer (n = 789) and number of clinical parameters: cancer localization, stage of the disease, treatment outcome, complications. Mann — Whitney two-tailed test and logistic regression models were used. Results: Lymphocyte counts (both absolute and relative) correlate with the cancer stage, and status of the disease, allowing differentiate patients with urological cancer, from healthy individuals, and from the cancer patients after radical surgery. In patients with kidney and bladder cancer, lymphocyte count allowed differentiate the stages of the disease. Lower rate of the reactivity of the patient to the cancer treatment is accurately predicted by the ALC and RLC: those in highest quartile for lymphocytes count have shorter postoperative recovery. Patients in lowest quartile demonstrated worst postoperative performance, including cases of early postoperative mortality due to weak somatic status. Conclusion: The study presents evidence that pretreatment lymphocyte count in the peripheral blood of patients with urological cancer is a sensitive marker of cancer stage, and the reactivity of the patient to the cancer treatment, which can be used in the pretreatment assessment of the patient. Key Words: urological cancer, lymphocytes, postoperative morbidity, reactivity, immune status assessment, treatment outcome.